CCAFS Annual Report 2020: CapDev Indicator (Annex) - Rose, Alison (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
These two excel sheets evidence the Capacity Development activities supported by CCAFS during 2020 and summarized in the CCAFS 2020 Annual Report.